Reprogramming cancer immunity with next-generation combination therapies - Kyriakidis, Nikolaos C.; Echeverría, Carolina E.; Bautista, Jhommara; Rivera-Orellana, Sebastián; Ramos Medina, María José; Salazar-Santoliva, Camila; Izquierdo-Condoy, Juan S.; Ortiz-Prado, Esteban; Guerrero, Santiago; López-Cortés, Andrés (Frontiers in cell and developmental biology, 2025)
Cancer immunotherapy has fundamentally reshaped oncology by harnessing the immune system to eliminate malignant cells. Immune checkpoint inhibitors targeting CTLA-4 and PD-1/PD-L1 have achieved durable remissions in select cancers, yet most patients exhibit resistance due to tumor heterogeneity, immunometabolic rewiring, and the immunosuppressive tumor microenvironment. To address these limitations, next-generation immunotherapies have emerged, targeting multiple layers of immune regulation. These include co-inhibitory and co-stimulatory checkpoint modulators, bispecific antibodies, adoptive cell therapies, cancer vaccines, oncolytic viruses, cytokine-based strategies, and synthetic immunomodulators that activate innate sensors. Nanotechnology and in vivo immune engineering further enhance specificity, reduce toxicity, and broaden applicability. Combination immunotherapy has become central to overcoming resistance, with rational regimens integrating ICIs, cytokines, vaccines, and targeted agents. Biomarker-guided strategies, leveraging tumor mutational burden, immune cell infiltration, and multi-omic profiling, are enabling personalized approaches. However, immune-related adverse events and variability in therapeutic responses necessitate predictive biomarkers and improved patient stratification. Emerging frontiers include microbiome-targeted interventions, chronotherapy, and AI-driven modeling of tumor-immune dynamics. Equally critical is ensuring global equity through inclusive trial design, diverse biomarker validation, and expanded access to cutting-edge therapies. This review provides a comprehensive analysis of multimodal immunotherapeutic strategies, their mechanistic basis, and clinical integration. By unifying innovation in immunology, synthetic biology, and systems medicine, next-generation cancer immunotherapy is poised to transition from a transformative intervention to a curative paradigm across malignancies.
Gesehen am 13.02.2026